Bevacizumab in late-onset radiation-induced myelopathy. (2nd February 2016) - Psimaras, Dimitri; Tafani, Camille; Ducray, Francois; Leclercq, Delphine; Feuvret, Loic; Delattre, Jean Yves; Ricard, Damien
Abstract : Objective: To investigate the efficacy of bevacizumab for treatment of late radiation-induced myelopathy. Methods: We studied all patients diagnosed with radiation-induced myelopathy presenting to 2 neuro-oncology centers between 2008 and 2012. All patients were treated with bevacizumab, after no clinical or radiologic improvement was achieved with conventional (in particular steroid) treatment. Result: This was a retrospective case study of 4 patients (2 women) with late-onset radiation-induced myelopathy who were each treated with 4 cycles of bevacizumab. The median delay from radiotherapy to myelopathy was 19 months (range 14–22 months). Initial treatment with steroids was unsuccessful in all 4 patients. Bevacizumab was introduced after a median of 4.8 months (range 4–5 months) from the onset of the neurologic symptoms. We observed stabilization of clinical outcome in 3 patients. Radiologic findings improved in all 4 patients. Conclusion: The use of bevacizumab resulted in radiologic improvement, but had only a modest effect on clinical outcome. Classification of evidence: This study provides Class IV evidence that for patients with late radiation-induced myelopathy unresponsive to steroids, bevacizumab improves radiologic but not clinical outcomes.